2011
DOI: 10.1257/aer.101.3.29
|View full text |Cite
|
Sign up to set email alerts
|

What Explains Changes in Retirement Plans during the Great Recession?

Abstract: We examine changes in subjective probabilities regarding retirement between the 2006 and 2008 waves of the Health and Retirement Study. Using a first-difference approach to eliminate individual heterogeneity, we find that the steep drop in asset prices in 2008 increased the reported probability of working at age 62 during the Great Recession. Increasing unemployment at least partly attenuated this effect, but subjective probabilities of working did not respond to changes in housing markets. Older workers' prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 1 publication
0
50
1
Order By: Relevance
“…Similarly, Goda et al (2011) found that although stock market fluctuations do affect expected retirement ages for workers close to percent relative to the other two income groups-largely offset the dramatic differences in average DC balances shown in Table 2, and the income groups are much more similar on this relative basis.…”
Section: Retirement Account Wealth To Income Ratiosmentioning
confidence: 83%
“…Similarly, Goda et al (2011) found that although stock market fluctuations do affect expected retirement ages for workers close to percent relative to the other two income groups-largely offset the dramatic differences in average DC balances shown in Table 2, and the income groups are much more similar on this relative basis.…”
Section: Retirement Account Wealth To Income Ratiosmentioning
confidence: 83%
“…Our results are consistent to CPS data findings by Coile and Levine (2009) showing that retirement of workers aged 62-69 appear to be affected by longer-term changes in the stock market but not of workers aged 55-61. In addition, 2008 HRS data utilized by Goda et al (2011) show that a 10 % increase in the level in the S&P 500 leads to a 1.209 percentage point decrease in the probability of working after the age of 62. Faculty who ranked financial ability to retire as the most important factor in retirement decision relative to other factors delay retirement by 1.13 years more in light of the great recession.…”
Section: Resultsmentioning
confidence: 99%
“…They also found evidence that the wealth effect during this time period were in the 3-5 cents range of long run additional consumption spending for every additional dollar of wealth. Goda et al (2011) likewise find some evidence that retirement plans shifted during the great recession as illustrated by a significantly higher average probability of working at age 62 by HRS respondents in 2008 compared to 2006. Self-reported probabilities of working at age 62 and 65, and self-reported expected retirement age suggest that older workers planned to remain in the labor force and delay retirement.…”
mentioning
confidence: 82%
“…Moreover, households have more options to ensure themselves against the devastating effects of a financial disaster: they can decide to work longer years and increase their retirement benefits. Goda, Shoven and Slavov (2011) and McFall (2011) provide recent evidence that TDA participants respond to the sharp downturn of stock prices during the Great Recession by prolonging their working years. We leave the important question of savings in individual accounts and labor supply decisions in times of a stock market crash to future research.…”
Section: Discussionmentioning
confidence: 99%